Purification and determination of biological activity of a recombinant enterokinase - Kim Phuong, Luong; Thi Huyen, Do; Thu Hong, Le Thi (Vietnam Journal of Biotechnology, 2021)
Enterokinase is a serine protease in which the light chain containing catalytic domain plays a role for recognition and digestion of a specific peptide of tetra-amino acids. Thus, it has been commonly used in biotechnology to cleave a fusion partner in chimeric protein for releasing target protein. In previous publication, the light chain of enterokinase was expressed in fusion form with thioredoxin to generate chimeric protein Trx-ent. The insoluble Trx-ent was primarily refolded for biological activity of auto-digestion to release enterokinase. In this study, we purified and examined biological activity of light chain recombiant enterokinase. The Trx-ent was refolded in process with denaturation in guanidin and then suitable buffers. Subsequently, the enterokinase was purified by factionation with ethanol precipitation at concentration of 20% to achive purify of 82%. The content of enterokinase obtained was 15.6 mg in 1 liter of fermentation and thus the recovery efficiency reached 8.2%. The activity of the recombinant enterokinase using Trx-FliC fusion protein as substrate was 230 units/µg, equivalent to the enterokinase activity of Invitrogen. This result is potential for application of the recombinant enterokinase in recombinant protein production.